Phosphorylated septin 3 delocalizes from the spine base and facilitates endoplasmic reticulum extension into spines via myosin-Va - Natsumi Ageta-Ishihara; Masato Mizukami; Itsuki Kinoshita; Yurika Asami; Tomoki Nishioka; Haruhiko Bito; Kozo Kaibuchi; Makoto Kinoshita (Molecular Brain)
Abstract Cytoskeletal remodeling drives morphological changes. Septin cytoskeleton assembles into hetero-oligomers. We previously demonstrated that late-phase long-term potentiation (L-LTP) induces smooth endoplasmic reticulum (sER) extension into dendritic spines via septin 3 (SEPT3), contributing to greater postsynaptic Ca2+ responses and enhanced activation of synaptically induced Ca2+ signaling. Sept3 −/− mice exhibit a reduced number of sER-containing spines and show impaired long-term spatial/object memory despite normal short-term memory. Additionally, SEPT3 binds the motor protein myosin-Va (MYO5A) upon elevated Ca²⁺ concentrations, facilitating sER extension from the dendritic shaft into the spine. MYO5A localizes on the sER membrane, while SEPT3 remains at the spine base, accumulating on sER upon electroconvulsive stimulation (ECS). However, the mechanism underlying SEPT3’s delocalization from the spine base and its cooperative role with MYO5A in sER extension remains unclear. In this study, we demonstrate that SEPT3 is phosphorylated in a stimulation-dependent manner. Phosphorylation at Thr211 releases SEPT3 from the spine base, enabling sER extension with constitutively active MYO5A mutant (MYO5A-CCtr). These findings provide molecular insight into the role of SEPT3 phosphorylation in regulating sER dynamics that sustain long-term spine activation.